UKURAN PERUSAHAAN DAN FAKTOR-FAKTOR YANG MEMENGARUHI AUDIT REPORT LAG - IVAN FERNALDY; FRESTIN CHRISNANTI (E-Jurnal Akuntansi TSM, 2022)
The purpose of this research is to determine the factors that affect audit report lag in manufacturing companies that were listed consistently on the Indonesian Stock Exchange from 2018-2020. The data used in this research were from the financial statement of the manufacturing companies that were listed consistently from 2018-2020. The sampel of this research are 78 manufacturing companies. This research used multiple linear regression models to analyze data. This research results had proven that the profitability, leverage and tenure audit have an influence on audit report lag. While the others independent variables do not have a influence on audit report lag.